DETERMINASI OPINI AUDIT DENGAN PENEKANAN GOING CONCERN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Firdaus, Hendra (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT Going concern opinion accepted by a company represents the condition and events which arises auditor’s hesitation of the company’s going concern. Going concern audit opinion can be used as early warning to the user of financial statements in order to prevent mistakes on decision making. A number of research has been conducted concerning factors that influence to going concern audit opinion. Yet, its result keeps showing inconsistency. This study objective is to reinvestigate factors that influence going concern audit opinion. The factors used on this research are liquidity, leverage, profitability, company’s size, company’s growth, audit lag, and auditor client tenure.This research using sample of manucaturing companies listed on Indonesia Stock Exchange during 2012-2016. Based on purposive sampling, there are 30 manufacturing companies which fulfilled the sample requirements. Hypotesis testing on this research was done by the logistic regression analysis.The hypotesis testing showed that leverage have positive relationship to going concern audit opinion. Variables of profitability have negative relationship to going concern audit opinion. Variables of liquidity, company’s size, company’s growth, audit lag and auditor client tenure have no relationship to going concern audit opinion.